Interaksi Kelas Online pada Kurikulum Merdeka Belajar di Lingkungan Perguruan Tinggi - Ageng Satria Pamungkas; Al Ikhlas; Dikwan Moeis; Joni Wilson Sitopu; MS Viktor Purhanudin (Journal on Education, 2023)
Online learning that has been carried out so far cannot be separated from problems such as unstable internet networks, which result in less than optimal teaching and learning processes. In addition, there is still very limited research that examines online interactions so it needs to be carried out considering that the learning system will not necessarily be carried out normally with a face-to-face process in the classroom. The purpose of this research was to determine the interaction that occurred in the online class of STKIP Muhammadiyan Sungai Full students. The method used by researchers in this study is the mixed method (Mix Method). The sample used in this study was mathematics education students. Sampling is carried out by purposive sampling. The analysis was carried out with stages: making transcripts of teaching and learning processes, coding, classifying online class interaction patterns, model interaction characteristics FIAC (Flander Interaction Analysis Code) and model BIAS (Brown Interaction Analysis System).